Phase 2 results of lisocabtagene maraleucel in Japanese patients with relapsed/refractory aggressive B‐cell non‐Hodgkin lymphoma. (26th May 2022) - Makita, Shinichi; Yamamoto, Go; Maruyama, Dai; Asano‐Mori, Yuki; Kaji, Daisuke; Ananthakrishnan, Revathi; Ogasawara, Ken; Stepan, Lara; Schusterbauer, Claudia; Rettby, Nils; Hasskarl, Jens; Izutsu, Koji
Abstract: The autologous anti‐CD19 chimeric antigen receptor (CAR) T‐cell product, lisocabtagene maraleucel (liso‐cel), is administered at equal target doses of CD8 + and CD4 + CAR + T cells. This analysis assessed safety and efficacy of liso‐cel in Japanese patients with relapsed or refractory (R/R) aggressive large B‐cell lymphoma (LBCL) in Cohort 3 of TRANSCEND WORLD (NCT03484702). Liso‐cel (100 × 10 6 total CAR + T cells) was administered 2–7 days after lymphodepletion. The primary efficacy endpoint was objective response rate (ORR; Lugano 2014 criteria) assessed by an independent review committee. Fourteen patients were enrolled; 10 received liso‐cel infusion (median time to liso‐cel availability, 23 days) and were evaluable at data cutoff (median follow‐up, 12.5 months). Grade ≥ 3 treatment‐emergent adverse events were neutropenia (90%), leukopenia (80%), anemia (70%), and thrombocytopenia (70%). All‐grade cytokine release syndrome (CRS) was observed in 50% of patients, though no grade ≥3 CRS events were reported. Grade 1 neurological events occurred in 1 patient but were resolved without any intervention. Prolonged cytopenia (grade ≥ 3 at day 29) was reported for 60% of patients. The ORR was 70%, and complete response rate was 50%. The median duration of response was 9.1 months (95% confidence interval [CI], 2.1—not reached), and overall survival was 14.7 months (95% CI, 1.7—not reached). One patient diagnosed with central nervous system involvement after screening but before liso‐cel infusion, responded to liso‐cel. Liso‐cel demonstrated meaningful efficacy and a manageable safety profile in Japanese patients with R/R LBCL. Abstract : This analysis assessed safety and efficacy of lisocabtagene maraleucel (liso‐cel), an autologous CD‐19‐directed CAR T‐cell product, in Japanese patients with R/R aggressive LBCL in Cohort 3 of TRANSCEND WORLD (NCT03484702). Liso‐cel demonstrated meaningful efficacy and a manageable safety profile in Japanese patients with R/R LBCL. We also report the first case of a patient who was diagnosed with secondary CNS lymphoma and achieved a response following treatment with liso‐cel.